2011
DOI: 10.1038/jid.2011.140
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Evaluation of Local JAK1 and JAK2 Inhibition in Cutaneous Inflammation

Abstract: JAKs are required for signaling initiated by several cytokines (e.g., IL-4, IL-12, IL-23, thymic stromal lymphopoietin (TSLP), and IFNγ) implicated in the pathogenesis of inflammatory skin diseases such as psoriasis and atopic dermatitis (AD). Direct antagonism of cytokines, such as IL-12 and IL-23 using ustekinumab, has proven effective in randomized studies in psoriasis patients. We hypothesized that local inhibition of cytokine signaling using topical administration of INCB018424, a small molecule inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
77
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(80 citation statements)
references
References 39 publications
2
77
0
1
Order By: Relevance
“…Corresponding to the scratching behavior results, topical application of each JAK inhibitor significantly inhibited the pruritogen-evoked cytokine secretions, including IL-31, TNFa, and TSLP, in the affected skin 30 minutes after TDI challenge. The antiinflammatory effects in allergic dermatitis by topical application of JAK inhibitors are also supported by the recently published study using topical application of the JAK1/JAK2 inhibitor ruxolitinib in a guinea pig model of delayed-type hypersensitivity (Fridman et al, 2011). According to the results from cytokine determinations of TDI-challenged ear skin, topical application of JAK inhibitors markedly inhibited the production of proinflammatory Th2 cytokines, including IL-1b, IL-4, IL-6, and TARC.…”
Section: Availability Of Jak Inhibitors On Allergic Dermatitismentioning
confidence: 53%
“…Corresponding to the scratching behavior results, topical application of each JAK inhibitor significantly inhibited the pruritogen-evoked cytokine secretions, including IL-31, TNFa, and TSLP, in the affected skin 30 minutes after TDI challenge. The antiinflammatory effects in allergic dermatitis by topical application of JAK inhibitors are also supported by the recently published study using topical application of the JAK1/JAK2 inhibitor ruxolitinib in a guinea pig model of delayed-type hypersensitivity (Fridman et al, 2011). According to the results from cytokine determinations of TDI-challenged ear skin, topical application of JAK inhibitors markedly inhibited the production of proinflammatory Th2 cytokines, including IL-1b, IL-4, IL-6, and TARC.…”
Section: Availability Of Jak Inhibitors On Allergic Dermatitismentioning
confidence: 53%
“…12) Due to their ability to selectively modulate immune function, targeted JAK inhibitors are attractive candidates for some skin diseases such as psoriasis and atopic dermatitis. [13][14][15] Our computer simulation result suggested that EGCG may bind to JAK2 protein (Fig. 1C).…”
Section: Egcg Inhibited Janus Kinase (Jak)2 Activity In Vitromentioning
confidence: 99%
“…The JAK family is composed of four tyrosine kinases -JAK1, JAK2, JAK3, and tyrosine kinase 2 (TYK2) (Fridman et al, 2011). Members of the JAK family are essential for signaling by many cytokines and growth factors following their binding to specific receptors on the cell surface.…”
Section: Janus-associated Kinase (Jak) Inhibitorsmentioning
confidence: 99%